The interdependence of gold, US dollar and stock market in the context of COVID-19 pandemic: an insight into analysis in Asia and Europe - Oanh Tran; Ha Nguyen (Cogent Economics & Finance)
Using the panel data vector autoregression (PVAR) model, this study examines the correlation between the stock market, gold price and USD exchange rate in the context of the COVID-19 pandemic in 55 Asian and 32 European countries from 11 March 2021 to 29 October 2021. The results of Granger causality test show that in Asian countries, there is a bidirectional causality between stock market and gold price. In addition, there is a unidirectional relationship between the stock market and the USD exchange rate, while the gold price and the USD exchange rate are completely independent of each other. Meanwhile, in European countries, stock market, gold price and USD exchange rate have a causal relationship at 1% significant level. The results of the impulse-response function analysis show that, in Asia, the stock market has a negative impact on the gold price and a positive effect on the USD exchange rate. In Europe, the stock market has a negative impact on the other two markets in the short term. The variance decomposition results suggest that, in Europe, the stock market return explains 2.5% for the gold price shock and 6.2% for the USD exchange rate shock from the tenth period. Meanwhile, these figures in the Asian countries are 1.6% and 3.2%, respectively.